2020
DOI: 10.1155/2020/2829854
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Herbal Mouthwashes on Plaque and Inflammation Control for Patients with Gingivitis: A Systematic Review and Meta‐Analysis of Randomised Controlled Trials

Abstract: Objective. The aim of this study was to evaluate the overall effects of herbal mouthwashes as supplements to daily oral hygiene on plaque and inflammation control compared with placebos and chlorhexidine (CHX) mouthwashes in the treatment of gingivitis. Methods. PubMed, EMBASE, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, and grey literature databases were searched. Only randomised controlled trials (RCTs) comparing herbal mouthwashes with placebos or CHX in the dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 47 publications
(117 reference statements)
1
39
0
1
Order By: Relevance
“…[ 30 ] Evidence from the literature shows the short-term and long-term efficacy of using adjunctive anti-plaque chemical agents. [ 20 21 , 31 ] A systematic review of clinical studies also confirmed the improvement of gingival health and the safety of alcohol-free, EO mouth rinses in comparison to other mouth rinses. [ 17 20 ] The efficacy of EO mouth rinse with and without alcohol did not show a significant difference concerning the reduction of plaque and gingivitis.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…[ 30 ] Evidence from the literature shows the short-term and long-term efficacy of using adjunctive anti-plaque chemical agents. [ 20 21 , 31 ] A systematic review of clinical studies also confirmed the improvement of gingival health and the safety of alcohol-free, EO mouth rinses in comparison to other mouth rinses. [ 17 20 ] The efficacy of EO mouth rinse with and without alcohol did not show a significant difference concerning the reduction of plaque and gingivitis.…”
Section: Discussionmentioning
confidence: 89%
“…[ 16 17 18 ] Various anti-plaque agents with different formulation such as chlorhexidine, stannous fluoride, essential oils (EO), cetylpyridinium chloride (CPC), and tricosan have been assessed. [ 19 20 21 22 23 ] Systematic review and meta-analysis have also indicated that mouth rinses significantly improved gingival inflammation, bleeding on probing, and plaque scores. [ 20 21 ] In addition, several studies have shown that EO containing mouth rinse has superior anti-plaque and antigingivitis effects than other mouth rinses and could be an alternative to chlorhexidine rinse as adjuncts to oral hygiene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29,30 The herbal mouthwashes and chemical mouthwashes have been proved to be equally effective in reducing plaque and gingivitis. 31,32 In a systematic review done by Jangid et al in 2014, among 17 articles, 14 showed similar efficacy of the mouthwashes, one study showed better result with Triphala mouthwash and two studies showed better result with chlorhexidine.Chlorhexidine is the gold standard mouthwash used in dentistry. On long term use, it causes staining of teeth and restorations.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method lacks complete and efficient removal of plaque, especially from the interproximal areas of the teeth. [ 4 5 ] This can be attributed to poor manual dexterity and lack of motivation, especially among children. [ 6 ] Bacteria colonizing on soft tissues also serve as a major source of micro-organisms on the tooth surface.…”
Section: Introductionmentioning
confidence: 99%